Integrating the Whoop It Up Strategy with the AIR (Auditory, Intellectually, Repetition) Learning Model in Arabic Language Learning - Taufik, Taufik; Febriani, Nailin Nabilah; Dimyathi, Muhammad Afifudin; Abdullah, Rafidah Binti Hj (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This research comprehensively describes implementing the